Feasibility study on early identification of freshness decay of fresh‐cut kiwifruit during cold chain storage by Fourier transform‐near infrared spectroscopy combined with chemometrics. Issue 7 (31st May 2022) - Wang, Huxuan; Wang, Cong; Peng, Zhonghua; Sun, Hongmin
Abstract : Abstract: This work mainly aimed to evaluate the feasibility of Fourier transform‐near infrared spectroscopy (FT‐NIRS) combined with chemometrics in early identification of freshness decay of fresh‐cut kiwifruit during simulated cold chain storage, with organoleptic evaluation as a reference. By linear discriminant analysis, the freshness decay could be identified after only 2 days of cold storage, corresponding to freshness level of 3.41 ± 0.27 N (hardness), 0.70 ± 0.05 g/kg (total acid), 8.62 ± 0.06 g/100 g (reducing sugars), 62.04 ± 1.03 mg/100 g (vitamin C) and 2.05 ± 0.11 log10 CFU/g (total plate count). Organoleptic evaluators could not perceive the freshness decay that occurred after 2 days of cold storage. Moreover, the freshness decay could be well quantitatively predicted by partial least squares regression, with low RMSE p (0.18–05.42) and high R 2 (0.90–0.96). FT‐NIRS appears to be a promising option for early warning of the freshness decay of fresh‐cut kiwifruit during cold chain storage, thereby preventing serious spoilage and ensuring fresh fruits for consumers. Practical Application: This work is based on the fact that fresh‐cut kiwifruit is prone to freshness decay under unstable cold chain conditions, using FT‐NIRS combined with chemometrics to identify the freshness decay early and rapidly, to a certain extent, early warn freshness decay and effectively prevent serious spoilage. The technology can be used for food regulatory agencies to monitor the freshness of fresh‐cut kiwifruit, and can also be applied for fruit processing enterprises and dealers to ensure the freshness and high quality of fresh‐cut kiwifruit.